2009
DOI: 10.1016/j.vetpar.2008.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcosis in pigs and intestinal infection with Echinococcus spp. in dogs in southwestern Lithuania

Abstract: Cystic echinococcosis is a major emerging zoonosis in many Eastern European and Asian countries. Post slaughter examinations of 684 pig livers in Lithuania revealed significantly higher numbers of Echinococcus granulosus infections in animals from family farms (13.2%; 95% CI 10.7-16.2) as compared with those from industrial farms (4.1%; 95% CI 0.8-11.5). The prevalence was also significantly higher in pigs older than 1 year than in younger ones. In addition, in 0.5% of the pigs from the family farms, infertile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
3
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 16 publications
4
40
3
6
Order By: Relevance
“…In our work, we found that 12 % of the dogs were infected with Taenia spp., while another group reported 21.8 % (16) of infection rate in the examined dogs (Beiromvand et al, 2011). An investigation in Lithuania showed signifi cant differences between a modifi ed McMaster method and the sieving-fl otation technique (Bružinskaitė et al, 2009). The sieving-fl otation technique, which was applied in the present study, is the appropriate method for concentration and detection of Taeniid eggs in stool samples.…”
Section: Discussionmentioning
confidence: 73%
“…In our work, we found that 12 % of the dogs were infected with Taenia spp., while another group reported 21.8 % (16) of infection rate in the examined dogs (Beiromvand et al, 2011). An investigation in Lithuania showed signifi cant differences between a modifi ed McMaster method and the sieving-fl otation technique (Bružinskaitė et al, 2009). The sieving-fl otation technique, which was applied in the present study, is the appropriate method for concentration and detection of Taeniid eggs in stool samples.…”
Section: Discussionmentioning
confidence: 73%
“…So far, four genotypes have been identified (Table 6). In Lithuania, E. intermedius (the pig strain, G7) with a farm dogepig cycle maintained by home slaughter practices has been predominantly observed in humans, pigs, cattle (sterile cysts) and in dogs (Bruzinskaite et al, 2009 (Oksanen and Lavikainen, 2015) and E. granulosus (G1) was found in a dog in Estonia(Marcinkut_ e et al, 2015) but the importance of this cycle is not known. In Poland, CE also occurs in animals (mainly pigs) and in humans; in people, E. intermedius (G7) and E. granulosus (G1) have been confirmed (autochthonous origin could not be excluded in two patients with G1) (Dybicz et al, 2015;Marcinkut_ e et al, 2015).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…The disease seems to be less prevalent in the UK, Central Europe, the Baltic States and the Scandinavian countries [5,6]. Surveys that addressed the incidence of CE over the last decade from central-eastern Europe has reported a relatively greater incidence in Romania (average incidence annual rate was 0.29 per 100,000 population) and Ukraine (0.30), whereas in Hungary (0.07), Poland (0.08) and Slovakia (0.10) lower numbers of human cases were documented [7].…”
Section: Introductionmentioning
confidence: 99%